Exploring student engagement and motivation : insights from a case competition - Vakulenko, Yulia; Hellström, Daniel ; 0000-0002-5681-3460 (Proceedings 2025 : 13:e pedagogiska inspirationskonferensen 4 december 2025, 2025)
This study evaluates the design choices of a two-day, industry-collaborative case competition at Campus Helsingborg and their effect on student motivation and engagement. Using pre and post Self-Determination Theory surveys, observations, and interviews we observed very high intrinsic (4.82/5) and extrinsic motivation (4.33/5). The perceived value of competition elements increased consistently after participation. Authentic briefs, mentor access, and a staged workflow with a public pitch to an external jury supported focus, learning, and professional readiness. Autonomy was enabled by open problem framing, competence by sequenced practice and iterative feedback, and relatedness by peer, mentor, and industry interactions.